n-Alkane biomarker, carbon, nitrogen and d13C data from the Barrow Peninsula (northern Alaska) before and after a one-year long incubation experiment - Fabian Seemann; Maren Jenrich; Justin Lindemann; Mikaela Weiner; Jens Hefter; Hanno Meyer; Guido Grosse; Benjamin Jones; Jens Strauss (PANGAEA, 2025)
We conducted a one-year long incubation experiment with sediment samples from the Barrow Peninsula (Utqiagvik, Alaska). In 2022 sediments were cored in two thermokarst lakes (East and West Twin Lake), one drained lake basin and an undisturbed upland. Additionally, sediment samples were taken from Elson Lagoon and a semi-open lagoon. On in total 20 chosen depths of all cores, n-alkane biomarker analyses were conducted. Parallelly, carbon, nitrogen and carbon isotopic analyses were carried out. Subsequently, ten lacustrine and terrestrial samples were incubated for one year under aerobic and dark conditions at 10°C. At the end of the experiment, the initial analyses were repeated. The biomarker and elemental analyses were conducted at the Permafrost Research Section (AWI Potsdam) and the isotope data has been generated in the ISOLAB Facility (AWI Potsdam).